2008
DOI: 10.1103/physrevlett.100.027204
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-Mechanically Induced Asymmetry in the Phase Diagrams of Spin-Glass Systems

Abstract: The spin-1/2 quantum Heisenberg spin-glass system is studied in all spatial dimensions d by renormalization-group theory. Strongly asymmetric phase diagrams in temperature and antiferromagnetic bond probability p are obtained in dimensions d ≥ 3. The asymmetry at high temperatures approaching the pure ferromagnetic and antiferromagnetic systems disappears as d is increased. However, the asymmetry at low but finite temperatures remains in all dimensions, with the antiferromagnetic phase receding to the ferromag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…It was then pointed out that this naturally leads to a higher transition temperature and effectively carries the ordering system to higher non-zero spin densities, the domain of second-order phase transitions. A similar microsegregation phenomenon, of the s i = ±1 states and of the s i = 0 state, has been seen in the low-temperature second-order transition between different ordered phases under quenched randomness [ 13].…”
Section: Enhancement Of Ferromagnetic Order and Critical Behaviormentioning
confidence: 68%
“…It was then pointed out that this naturally leads to a higher transition temperature and effectively carries the ordering system to higher non-zero spin densities, the domain of second-order phase transitions. A similar microsegregation phenomenon, of the s i = ±1 states and of the s i = 0 state, has been seen in the low-temperature second-order transition between different ordered phases under quenched randomness [ 13].…”
Section: Enhancement Of Ferromagnetic Order and Critical Behaviormentioning
confidence: 68%
“…Similar previous studies, on other spin-glass systems, are reported in Refs. [12,13,[40][41][42][43][44][45][46][47]. Figure 1 shows a calculated sequence of phase diagram cross sections for the left-chiral (c = 0) (top row) and quenched random left-and right-chiral (c = 0.5) (bottom row) systems with, in both cases, quenched random ferromagnetic and antiferromagnetic interactions.…”
Section: Renormalization-group Method: Migdal-kadanoff Approximamentioning
confidence: 99%
“…However, as noted before [45], the local summation in position-space technique used here has been qualitatively, near-quantitatively, and predictively successful in a large variety of problems, such as arbitrary spin-s Ising models [46], global BlumeEmery-Griffiths model [47], first-and second-order Potts transitions [48,49], antiferromagnetic Potts critical phases [50,51], ordering [6] and superfluidity [52] on surfaces, multiply reentrant liquid crystal phases [53,54], chaotic spin glasses [55], random-field [56,57] and random-temperature [58,59] magnets, including the remarkably small d = 3 magnetization critical exponent β of the random-field Ising model, and high-temperature superconductors [60]. Thus, this renormalization-group approximation continues to be widely used [61][62][63][64][65][66][67][68][69][70][71][72][73][74].…”
Section: Renormalization-group Transformation: Migdal-kadanoff Amentioning
confidence: 99%
“…We effect this procedure numerically, by representing each probability distribution by histograms, as in previous studies [62,[64][65][66]68,69,72,74]. The probability distributions of two interactions P 0 (J + ,J − ), P + (J 0 ,J − ), and P − (J + ,J − ) are represented via bivariate histograms with two-dimensional vectors (J + ,J − ) for P 0 , etc.…”
Section: Renormalization-group Transformation: Migdal-kadanoff Amentioning
confidence: 99%
See 1 more Smart Citation